2022
DOI: 10.1155/2022/6138941
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of MCF2L Promoted the Ferroptosis of Hepatocellular Carcinoma Cells through PI3K/mTOR Pathway in a RhoA/Rac1 Dependent Manner

Abstract: Backgound. Multiple patients with hepatocellular carcinoma (HCC) received sorafenib therapy presented primary or secondary chemoresistance. The underlying mechanisms of chemoresistance are rather vague, ferroptosis is a new kind of cell death, and its discovery provides new opportunities to overcome sorafenib resistance. Therefore, it is essential to investigate the regulators of ferroptosis and implement a corresponding therapy strategy. Methods and Results. The levels of MCF2L were detected by PCR and wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…6B ). In addition, many GTPase regulatory genes were found specifically increased in humans, including MCF2L and RASGRF2 , which are known to regulate RAC1 , and SPATA13 , which enables guanyl-nucleotide exchange factor activity [ 34 , 35 ]. In contrast, we observed that signaling pathways mainly dealing with energy metabolism were commonly regulated in patients with heart disease as well as in mouse models.…”
Section: Resultsmentioning
confidence: 99%
“…6B ). In addition, many GTPase regulatory genes were found specifically increased in humans, including MCF2L and RASGRF2 , which are known to regulate RAC1 , and SPATA13 , which enables guanyl-nucleotide exchange factor activity [ 34 , 35 ]. In contrast, we observed that signaling pathways mainly dealing with energy metabolism were commonly regulated in patients with heart disease as well as in mouse models.…”
Section: Resultsmentioning
confidence: 99%
“…( 110 ), curcumin promoted iron apoptosis in colorectal cancer by controlling the expression of vital iron apoptosis indicators Fer 1, SLC7A11, GSH, MDA, and ROS through the PI3K/mTOR pathway. Recent studies have shown that the mTOR-related signaling system can either promote or inhibit ferroptosis in hepatocellular carcinoma cells ( 111 , 112 ). For instance, HU et al.…”
Section: Mechanisms Of Ferroptosis Regulationmentioning
confidence: 99%
“…Additionally, according to Chen et al (110), curcumin promoted iron apoptosis in colorectal cancer by controlling the expression of vital iron apoptosis indicators Fer 1, SLC7A11, GSH, MDA, and ROS through the PI3K/mTOR pathway. Recent studies have shown that the mTOR-related signaling system can either promote or inhibit ferroptosis in hepatocellular carcinoma cells (111,112). For instance, HU et al (113) found that miR-21-5p controlled the AKT/mTOR signaling pathway through MELK in vivo, reducing iron apoptosis in hepatocellular carcinoma cells.…”
Section: Mechanistic Target Of the Rapamycinmentioning
confidence: 99%